Development and validation of a microRNA‐based diagnostic assay for classification of renal cell carcinomas. Issue 3 (26th March 2013) - Spector, Yael; Fridman, Eddie; Rosenwald, Shai; Zilber, Sofia; Huang, Yajue; Barshack, Iris; Zion, Orit; Mitchell, Heather; Sanden, Mats; Meiri, Eti
Abstract : Renal cancers account for more than 3% of adult malignancies and cause more than 13, 000 deaths per year in the US alone. The four most common types of kidney tumors include the malignant renal cell carcinomas; clear cell, papillary, chromophobe and the benign oncocytoma. These histological subtypes vary in their clinical course and prognosis, and different clinical strategies have been developed for their management. In some kidney tumor cases it can be very difficult for the pathologist to distinguish between tumor types on the basis of morphology and immunohistochemistry (IHC). In this publication we present the development and validation of a microRNA‐based assay for classifying primary kidney tumors. The assay, which classifies the four main kidney tumor types, was developed based on the expression of a set of 24 microRNAs. A validation set of 201 independent samples was classified using the assay and analyzed blindly. The assay produced results for 92% of the samples with an accuracy of 95%. Highlights: A lab developed test using 24 microRNAs on an array platform classifies the four main kidney tumor types. An independent cohort of 201 samples was used to validate the test with 95% accuracy. Inter‐laboratory reproducibility testing resulted with 100% inter‐laboratory concordance.